2017
DOI: 10.21037/jtd.2017.10.52
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extreme obesity on outcomes after left ventricular assist device implantation

Abstract: Despite an increased risk of early morbidity in patients with extreme obesity, long term survival was not significantly different between the BMI groups. Careful consideration is recommended when evaluating patients with an excessive BMI for LVAD therapy although it should not be a contraindication for device placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…4 Recent studies have suggested that increased BMI does not have an impact on LVAD implantation outcomes. 5 Our findings are like those reported by previous authors, as BMI did not show any association with mortality.…”
Section: Discussionsupporting
confidence: 92%
“…4 Recent studies have suggested that increased BMI does not have an impact on LVAD implantation outcomes. 5 Our findings are like those reported by previous authors, as BMI did not show any association with mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The increasing incidence and prevalence of obesity is accompanied by life‐limiting comorbidities including the metabolic syndrome, pulmonary hypertension, hypercoagulable state, atherosclerotic disease, arrhythmias, and HF. Our work confirms the results of several recent studies, which failed to detect a significant difference in short‐term and intermediate postoperative survival between obese and nonobese LVAD recipients . However, higher rates of hospital readmissions and complications such as AKI , infection , thromboembolism , and PT are often present in the obese cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Obesity has been shown to increase morbidity, mortality, and overall system costs in certain types of general cardiac surgery ; however, published outcomes of obese patients following LVAD implantation are limited. Although the risks of complications related to obesity, such as thromboembolic events , device infection , and RV failure have been reported, these studies suggest conflicting conclusions in regards to the effect of obesity on mortality. The development of more durable LVAD technologies has improved overall survival and complication rates, even as the cases accepted for surgery have become more complicated .…”
Section: Introductionmentioning
confidence: 99%
“…A further study by Mohamedali et al conducted on 288 HMII and HVAD patients found that despite higher readmission rates, obesity was not associated with a decrease in survival rates at three years post LVAD implantation [ 25 ]. Greater insight was provided by Yost et al, who in their analysis also included a group of extremely obese (BMI > 35 kg/m 2 ) patients receiving HMII and HVAD LVADs [ 26 ]. On assessment of 30-day, 1-, and 2- years follow neither the obese nor the extremely obese showed any significant difference in survival ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…On assessment of 30-day, 1-, and 2- years follow neither the obese nor the extremely obese showed any significant difference in survival ( Table 4 ). Postoperative adverse events and complications including length of stay, sternal infection, driveline/pocket infection, systemic infection, GI-bleeding, and neurological events were also found to be unvaried across groups in the study [ 26 ]. Nevertheless, studies in the past have found severely obese (BMI ≥ 35 kg/m 2 ) patients to have worse outcomes on LVAD.…”
Section: Discussionmentioning
confidence: 99%